Thermal Impact on Heavy Metal Bioavailability in Burnt Rocks of Waste Heap of Chervonohradska Coal-preparation Plant (Lviv Region, Ukraine) - Kochmar, Iryna; Karabyn, Vasyl; Stepova, Kateryna; Stadnik, Vitalii; Sozanskyi, Martyn (Geomatics and Environmental Engineering, 2024)
For effective waste management of mining industries is important to investigate their physical and mineralogical changes. For this purpose, X-raydiffraction (XRD), thermogravimetry (TG), derivative thermogravimetry (DTG), and differential thermal analysis (DTA) methods were used. Changes in the contents of mobile forms of heavy metals in rocks were investigated using an acetate-ammonium buffer solution with a pH of 4.8 after burning rocks at a temperature of 800–850°C. The obtained data indicated the significant role of the mineral composition in the thermal behavior of the rock samples and the subsequent influence of the thermal processes on the changes in the bioavailability of heavy metals.